Improving the Resident Educational Experience in a Level IV Neonatal/Infant Intensive Care Unit. Issue 6 (November 2020) - Handley, Sara C.; Pouppirt, Nicole; Zucker, Eric; Coughlin, Katherine A.; Ades, Anne
Abstract : Introduction: The neonatal/infant intensive care unit (N/IICU) at the Children's Hospital of Philadelphia is a 98-bed, level IV unit through which second-year pediatric residents rotate monthly. We developed a quality improvement project to improve the resident educational experience using goal setting. Primary objectives were to increase resident educational goal identification to 65% and goal achievement to 85% by June 2017. Secondary objectives were to (1) increase in-person feedback from fellows and/or attendings to 90% by June 2017 and (2) sustain improvements through June 2018. Methods: The quality improvement team developed a driver diagram and administered a baseline survey to 48 residents who had rotated through the N/IICU in the 18 months before the project. Plan-Do-Study-Act cycles targeted project awareness and trialing of 3 different methods to elicit goals and track feedback, from July 2016 through June 2018. Results: The baseline survey response rate was 52% (n = 25). Among 60 rotating residents, the median resident-reported rate of goal achievement increased from 37.5% to 50%, and residents receiving in-person feedback increased from 25% to 50%. Of the 63% (n = 38) of residents who participated in data collection, goal identification and achievement increased from 38% to 100% between academic year 2016 and academic year 2017, and in-person feedback increased from 24% to 82%. Conclusions: Instituting a goal-setting framework for residents during their N/IICU rotation increased goal achievement and in-person feedback. Consistent resident participation in postrotation data collection made measuring project outcomes challenging. These data support goal-oriented learning as an approach to enhance learner engagement and improve goal achievement. Abstract : Supplemental Digital Content is available in the text.